Relative Age Effect on Youth Female Volleyball Players: A Pilot Study on Its Prevalence and Relationship With Anthropometric and Physiological Characteristics - Papadopoulou, Sophia D.; Papadopoulou, Sousana K.; Rosemann, Thomas; Knechtle, Beat; Nikolaidis, Pantelis T. (Frontiers in Psychology, 2019)
Relative age effect on youth female volleyball players: Prevalence and relationship with anthropometric and physiological characteristics